Thermal Runaway of a Li-Ion Battery Studied by Combined ARC and Multi-Length Scale X-ray CT. Issue 9 (2nd April 2020) - Patel, Drasti; Robinson, James B.; Ball, Sarah; Brett, Daniel J. L.; Shearing, Paul R.
Abstract : Lithium ion battery failure occurs across multiple length scales. In this work, the properties of thermal failure and its effects on electrode materials were investigated in a commercial battery using a combination of accelerating rate calorimetry (ARC) and multi-length scale X-ray computed tomography (CT). ARC measured the heat dissipated from the cell during thermal runaway and enabled the identification of key thermal failure characteristics such as onset temperature and the rate of heat generation during the failure. Analysis before and after failure using scanning electron microscopy (SEM) and X-ray CT were performed to reveal the effects of failure on the architecture of the whole cell and microstructure of the cathode material. Mechanical deformations to the cell architecture were revealed due to gas generation at elevated temperatures (>200 °C). The extreme conditions during thermal runaway caused the cathode particles to reduce in size by a factor of two. Electrode surface analysis revealed surface deposits on both the anode and cathode materials. The link between electrode microstructure and heat generation within a cell during failure is analysed and compared to commercially available lithium ion cells of varying cathode chemistries. The optimisation of electrode designs for safer battery materials is discussed.